Multicriteria analysis and logistical grouping method for selecting areas to consortium landfills in Paraiba do Sul river basin, Brazil - Senkiio, Caroline Souza [UNESP]; Ramos, Ana Paula Marques; Simões, Silvio Jorge Coelho [UNESP]; Mendes, Tatiana Sussel Gonçalves [UNESP] (My University, 2022)
The geographical nature and environmental, operational, and socioeconomic factors involved in the complex task of selecting landfill sites require the use of Multi-Criteria Decision Analysis (MCDA) in a Geographic Information System (GIS) environment. Moreover, GIS-based route analysis can optimize the process of area selection for landfills that attend to more than one municipality, i.e., consortium landfills. This study presents a methodological approach integrating MCDA and logistical analysis to propose suitable areas for consortium landfills. The region of the Paraíba do Sul basin, southeast of Brazil, was selected as a case of study. The proposed method uses the Analytical Hierarchy Process (AHP) with fuzzy logic to select suitability areas to landfill. Additionally, a logistical method of municipalities clusters involving criteria based on localization, number of municipalities, distance, and the minimum area is applied to select suitable areas that serve more than one municipality. The findings demonstrated that 69% of the study area is inadequate to support a consortium landfill installation. From the remaining areas, 26.03% were considered highly suitable. Among these, a scenario with 11 areas was selected to be destined to consortium landfills to attend the region for 20 years. Selecting areas of high suitability and evaluating these areas for consortia formation contribute to the minimization of negative impacts resulting from the implementation and operation of landfills. It is concluded that the proposed approach can support this task efficiently and it is recommended that it be employed in other regions that also face the critical problem of defining areas for consortia formation.
Keywords: Analytical hierarchy process; Fuzzy logic; Geographic information system; Logistical grouping; Municipal solid waste; Origin–destination cost matrix